Budgeting as a tool for managing enterprise strategy (Вестник КазНУ. Серия Экономическая, 2017)
In this article, the problem of effective conducting budgeting as one of managementtools which costs in the center of attention of scientists as for today theorganizations quite often practice creation of budgets is considered. However,now scientists did not give unambiguous definition and purpose of budgetingand therefore the budgeting system seldom brings to the entities desirable result.The purpose of this article to analyse efficiency of budgeting which showedthat it is possible to allocate basic reasons of this problem: lack of the accuratepurpose of a budgeting system in case of its implementation at the entity; a gapbetween strategic objectives of the entity and the purposes of a budgeting system;lack of support of implementation process of strategy by budgeting.As a result of our research we found out that enhancement of a budgetingsystem by means of implementation of an algorithm of creation ofbudgets in it gives the chance of increase in efficiency of implementationprocess of strategy of the entity as: orients it to implementation process ofstrategy of the entity; the ordered system of creation of budgets will concentrateon value increase of the entity.